Sustainable Education in Natural Sciences, Economics and Technology - Angelos Stoumpos; Rodanthi Stoumpou; Vassilis Tsiantos (Journal in Teaching and Education Area, 2026)
The sustainability of knowledge is a critical factor for natural sciences, technology and economic education, as it is directly linked to the creation and management of innovation and the support of sustainable development. The article examines the dimensions of knowledge – explicit and tacit – and their role in the learning process and in educational ecosystems. This study adopts a qualitative research approach based on a narrative literature review and conceptual analysis. It synthesizes existing literature on knowledge creation, knowledge management, sustainability, and educational systems in order to explore the role of sustainable knowledge in modern education. The importance of knowledge management and the preservation of intellectual capital in educational organizations is analyzed, as well as the human, organizational and environmental factors that influence the transfer and exchange of knowledge. In addition, the relationship between knowledge, technology, innovation and sustainable development is explored, with an emphasis on the challenges of less developed countries and the transition to a global knowledge economy. The framework of the knowledge economy is presented and the role of education, innovation and information technologies as fundamental pillars for sustainability is highlighted. Finally, it emerges that the success of educational organizations depends on their ability to create, disseminate and utilize sustainable knowledge, creating a competitive advantage and contributing to the formation of creative, innovative and socially responsible citizens.